2013
DOI: 10.1371/journal.pone.0070830
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vectors’ Risk-Spreading Strategies and Environmental Stochasticity on the Epidemiology and Evolution of Vector-Borne Diseases: The Example of Chagas’ Disease

Abstract: Insects are known to display strategies that spread the risk of encountering unfavorable conditions, thereby decreasing the extinction probability of genetic lineages in unpredictable environments. To what extent these strategies influence the epidemiology and evolution of vector-borne diseases in stochastic environments is largely unknown. In triatomines, the vectors of the parasite Trypanosoma cruzi, the etiological agent of Chagas’ disease, juvenile development time varies between individuals and such varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…More generally, deterministic approaches are less relevant for analyzing extinction probabilities than stochastic approaches [36] . Even if parameter estimation and model comparison is more complex (despite the recent advances obtained using Approximate Bayesian Computing methods [37] ), a stochastic implementation of the model should allow analyzing the extinction probability of RVFV circulation in the study area [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
“…More generally, deterministic approaches are less relevant for analyzing extinction probabilities than stochastic approaches [36] . Even if parameter estimation and model comparison is more complex (despite the recent advances obtained using Approximate Bayesian Computing methods [37] ), a stochastic implementation of the model should allow analyzing the extinction probability of RVFV circulation in the study area [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
“…The only contribution sets under the light of life‐history evolution is by Pelosse et al. (), and it shows that vector's risk spreading strategies can speed up the invasion of virulent strains in a stochastically variable environment. Although truly inspiring, this paper relies on numerical analyses that do not seek to provide the simple (analytical) foundations for a broad theory of T. cruzi virulence evolution.…”
Section: Trypanosoma Cruzi Diversity and Virulence Evolutionmentioning
confidence: 99%
“…Today, the persistence of vector transmission in many other places (Patterson & Guhl, ) raises new issues for the future of Chagas disease's control. These emerging challenges are associated with typical evolutionary processes that could significantly change the local and/or global patterns of the disease epidemiology: (i) the rise of insecticide resistance (Mougabure‐Cueto & Picollo, ; Pessoa, Vinãs, Rosa, & Diotaiuti, ), (ii) the adaptation of nondomiciliated vectors to the human habitat (Almeida et al., ; Reyes‐Lugo & Rodriguez‐Acosta, ; Waleckx, Gourbière, et al., ), and (iii) the potential evolution of T. cruzi virulence (Bull & Lauring, ; Pelosse et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Development delays are a well-studied aspect of evolutionary strategies, and have been analyzed in insect pest species, such as the chestnut weevil (Rajon et al, 2014); however, they have been scarcely investigated in disease vectoring insects (Menu et al, 2010). Recently, Pelosse et al (2013) showed that bet-hedging strategies in Chagas disease vectors potentially affect the epidemiology and evolution of the parasite Trypanosoma cruzi Chagas, the etiologic agent of Chagas disease, which ultimately affects the control of Chagas disease transmission. These authors also demonstrated that environmental stochasticity associated with bet-hedging strategies in triatomine development time may increase the prevalence of vector-borne Chagas disease, favoring more virulent strains of parasites in a relatively short evolutionary time scale.…”
Section: Introductionmentioning
confidence: 99%